Nature and effect of Alternaria spp. complex from wheat grain on germination and disease transmission - Perelló, Analía Edith (2013)
Diseases caused by Alternaria sp. are among the most common diseases of crops throughout the world. Alternaria sp. is a common component of the flora of wheat seed. Although isolation of Alternaria sp. from wheat (Triticum aestivum) seed has been reported in Argentina, development of the Alternaria blight in plants from infected seeds has not been demonstrated experimentally. Seed transmission of strains belonging to Alternaria tenuissima, A. alternata, A. infectoria, A. triticina, A. chlamydospora and related genera like Embellisia and Ulocladium sp. on wheat were investigated in the Argentinean growing area, on wheat cultivars Klein Escorpión and Buck Poncho. A. tenuissima was the dominant fungus in black pointed kernels. Transmission of all 42 seed-borne members of Alternaria complex from seeds to seedlings artificially inoculated was detected by trays seedling symptoms test. Among the fungi tested most isolates of Alternaria, Embellisia sp. and Ulocladium sp. produced distinct seed rot and seedling infection symptoms. This confirmed the seed-borne nature of these fungi. In each wheat cultivar tested inoculated seeds appreciably reduced their germination. The emerging coleoptile is externally infected by hyphal growth from the infected pericarp. Typical disease symptoms on the seedlings were exhibited. Recovery of the fungi from asymptomatic coleoptiles was also possible. Transmission efficiency varies with wheat cultivar and ranges from 0 to 92%. These results suggest that infected seed and seed transmission represents a mode of primary source of infection from which these microorganisms can start epidemics to the wheat crop and for dispersal of fungal strains to new areas.